Demonstrasi Pembuatan Pakan Pellet Sebagai Alternatif Pakan Di Musim Kemarau Kepada Kelompok Peternak Bolotomo, Desa Wingkosigromulyo, Kabupaten Purworejo - Nanda Juniarti; Tri Wahyu Yuliana; Ahmad Fadil Mubarok; Indria Nur Khasanah; Bintang Nanggala Basa (Lembaga Pengembangan Kinerja Dosen, 2024)
The Bolotomo cattle breeder group in Wingkosigromulyo Village, Nkombol District, Purworejo Regency, has been established since 2010 with the help of subsidies from the local Livestock Service. Initially, they focused on producing organic fertilizer, but switched to the feeder cattle and meat business because the selling price of fertilizer was low. Livestock management is still traditional, and concentrate feed is rarely used because it is expensive and difficult to obtain. In the dry season, food availability is limited, and rice straw and field grass are the main food sources. The service activity by Tidar University students aims to help farmer groups overcome the feed crisis with technology for making pellets from local materials. Demonstration of making pellets using a mixture of calliandra leaf flour, rice bran, pineapple peel, molasses and tapioca flour. Pellets have the advantage of improving feed quality, consumption efficiency and shelf life. Farmers also shared their experiences and expressed the need for processing livestock waste, such as biogas plants, to reduce pollution and increase income. Integration between the agriculture, fisheries and livestock sectors is the focus for sustainable development.